Implementation of Easy Wadiah Savings Products at BSI KCP Sidoarjo Krian in the Perspective of DSN-MUI Fatwa No. 02/DSN-MUI/IV/2000 - Nisa Rahmayani; Arin Setiyowati Setiyowati; Rukhul Amin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the implementation of Easy Wadiah Savings products at Bank Syariah Indonesia (BSI) Sidoarjo Krian Branch Office (KCP) according to DSN-MUI Fatwa No. 02/DSN- MUI/IV/2000. This product uses the wadiah yad dhamanah contract, which is a fund deposit contract where the bank guarantees the security of funds without providing a guarantee of return. The approach used in this study is qualitative using case studies, interviews with the bank, namely Customer Service and customers, and examination of related documents. The results of the study indicate that the implementation of this product is in accordance with sharia principles as stated in the fatwa, as evidenced by the absence of interest, the existence of voluntary incentives from the bank, and the ease for customers to access their funds. However, there are still several obstacles because the public's understanding of the concept of the wadiah contract is still limited. Therefore, efforts are needed to educate and increase knowledge of sharia finance.